Huta Ginjang Dolok Site: An Indication Of The Early Residence Sisingamangaraja Dynasty At Lake Toba Based Ecological Considerations - SIMATUPANG, DEFRI ELIAS; Dyah Hidayati; Lolita Refani Lumban Tobing (Badan Riset dan Inovasi Nasional (BRIN), 2024)
Valleys and hills in Bakara, Humbang Hasundutan Regency, are the origins of the Sisingamangara Dynasty (the hereditary king for most of the Toba Batak ethnic community). The purpose of this study is to describe the implementation of the early Batak ethnic dwellings that thought of defense against enemy attacks while protecting the resources and environment of the area. This study uses a qualitative approach that uses data from archaeological excavations, observations, and interviews at one of the object locations in Bakara, namely Huta Ginjang Dolok. The results of the research description indicate that the location of Huta Ginjang Dolok has indeed proven to be one of the examples of early settlements in the Lake Toba area, which has several functions, including social functions related to traces of former settlements in locations located on hillsides. The ecological function is related to the abundance of clean mountain springs. The cultural function is related to the finding of human and livestock bones in archaeological excavations carried out during the research, and the economic function is related to the discovery of foreign currency, also found in the excavation activities during field activities.